Advances in Cancer Therapeutics: Conventional Thermal Therapy to Nanotechnology-Based Photothermal Therapy - Sangeeta Kumari; Nilesh Sharma; Shivendra V. Sahi (MDPI AG, 2021)
In this review, advancement in cancer therapy that shows a transition from conventional thermal therapies to laser-based photothermal therapies is discussed. Laser-based photothermal therapies are gaining popularity in cancer therapeutics due to their overall outcomes. In photothermal therapy, light is converted into heat to destruct the various types of cancerous growth. The role of nanoparticles as a photothermal agent is emphasized in this review article. Magnetic, as well as non-magnetic, nanoparticles have been effectively used in the photothermal-based cancer therapies. The discussion includes a critical appraisal of in vitro and in vivo, as well as the latest clinical studies completed in this area. Plausible evidence suggests that photothermal therapy is a promising avenue in the treatment of cancer.